The four loves - Lewis, C. S. (Clive Staples), 1898-1963. (New York : Harcourt Brace Jovanovich, 1991)
Analyzes the feelings and problems involved in different types of human love, including familial affection, friendship, passion, and charity.
Introduction -- Likings and loves for the sub-human -- Affection -- Friendship -- Eros -- Charity.
Reprint. Originally published: New York : Harcourt, Brace, 1960.
Keywords: Love -- Religious aspects -- Christianity